The (R)evolution Is Dead, Long Live the (r)evolution!. Issue 2 (1st December 2019) - Ritter, Daniel P.
Abstract : Responding to the debate that was carried on in recent issues of this journal, this article argues that the era of revolutions is not by any means over, but that an "evolution of revolution" has occurred over the past few decades that has fundamentally transformed what revolutions are. This development forces us to rethink how we approach revolutions as sociological phenomena. Instead of employing strict definitions that make sharp distinctions between revolutions and nonrevolutions, we are better served by more inclusive approaches to revolutionary change. The article outlines some of the ways in which revolutions have evolved and how we might go about understanding them.